Strengthening global partnerships for sustainable sickle cell disease care: insights from SickleInAfrica at the 77th United Nations General Assembly and the US-Africa Leaders’ Summit - Nicola Mulder; Victoria Nembaware; Vivian Paintsil; Emmanuel Peprah; Sarah Kiguli; Julie Makani; Josephine Mgaya; Siana Nkya; Raphael Zozimus Sangeda; Emmanuel Balandya; Catherine Chunda-Liyoka; Obiageli Eunice Nnodu; et al. (BMJ Global Health)
Background Addressing sickle cell disease (SCD) is crucial for achieving health-related Sustainable Development Goals, particularly in Africa. The region is significantly affected, with 78.7% of patients with SCD residing in sub-Saharan Africa and over 515 000 newborns diagnosed annually. Historically, African health systems have struggled to provide optimal care for patients with SCD, resulting in high under-5 mortality and severe childhood morbidity. Scientific innovations and stakeholder engagement offer hope for improving SCD outcomes.Objective To explore the role of high-level partnerships and scientific innovation in advancing SCD care and research in Africa, focusing on the contributions and strategic engagements of the SickleInAfrica, as highlighted at the 77th United Nations General Assembly (UNGA) and the US-Africa Leaders’ Summit.Approach SickleInAfrica, comprising eight countries, leverages a robust infrastructure for SCD research and care. The consortium has established a comprehensive SCD database and a patient registry in each of the consortium sites that includes demographic details, clinical diagnosis, management details and follow-ups/visits. Currently, over 34 000 patients with SCD are enrolled, making it the largest globally. It has also contextually adapted clinical guidelines for managing SCD for all levels of care. The high-level engagements at the 77th UNGA held in September 2022 in New York and the US-Africa Leaders’ Summit held in December 2022 in Washington DC promoted SCD awareness and partnerships. The UNGA session emphasised biomedical science, implementation research and partnerships in therapeutic development, while the US-Africa Leaders’ Summit session focused on Global Partnerships for SCD: Advancing Science and Technology for Health in Africa.Conclusions High-level engagements facilitate cross-border dialogues, underscoring the importance of partnerships from grassroots to global alliances. Key outcomes include increased awareness, policy advocacy and the establishment of SCD Centres of Excellence and genomics capacity-building initiatives. Sustainable efforts require robust partnerships, government involvement, community awareness and equitable access to advanced therapies.